A study of lesser pelvic parameters and their correlation with age by reformatted computed tomography in western Indian Gujarati female population - Ritesh K Shah; Jalpa N Desai; Ajay R Upadhyay (Wolters Kluwer Medknow Publications, 2018)
Background & aims: Pelvic parameters vary according to age, race and population. The study is aimed at assessing female pelvic parameters using reformatted 3D CT images, compare the obtained values with other studies and correlate these parameters with age. Material & Methods: Reformatted three-dimensional CT images were obtained from stored abdominopelvic computed tomography [CT] scan images. Image analysis software was used to determine various diameters of the lesser pelvis. Data were analysed to derive mean ± SD, SE, 95% CI, paired t test and Pearson correlation test were used for comparison and correlation of variables. Results: Mean± standard deviation of obstetric conjugate diameter was 10.94±1.18 cm, transverse diameter of inlet was 12.46±0.81 cm, sagittal diameter of midplane wasl 1.74±0.80 cm, interspinous diameter was 9.78±0.75 cm, sagittal diameter of outlet was 8.99±1.02 cm and intertuberous diameter was 10.69±0.86. All the parameters except sagittal diameter of midplane and interspinous diameter showed correlation with age. Conclusion: The present study provides reference values for various pelvic parameters in western Indian Gujarati female population. Parameters obtained in present study vary greatly from previous studies from other populations. The results demonstrated that significant age-related changes occurred in pelvic inlet and outlet parameters.